Modeling of gene regulatory networks: an annotated glossary - Avilash Singh Yadav; Nicholas J. Russell; Adriana I. Hernández; Alaina R. Petlewski; Arielle R. Johnson; Ayress D. Grinage; Barituziga Banuna; Clarice J. Guan; Elizabeth H. Mahood; Gordon C. Younkin; Hannah R. Thomas; Heather R. Phillips; et al. (Trends in Plant Science, 2026)

Correction to: Practical considerations for trace DNA recovery and detection of an invasive reptile across different deposition scenarios - Nathan Deliveyne; Tiara Kinanti Benyamin; Jeremy J. Austin; Kate Sanders; Phillip Cassey (Conservation Genetics Resources, 2025)

Practical considerations for trace DNA recovery and detection of an invasive reptile across different deposition scenarios - Nathan Deliveyne; Tiara Kinanti Benyamin; Jeremy J. Austin; Kate Sanders; Phillip Cassey (Conservation Genetics Resources, 2025)
Trace DNA detection methods are increasingly applied to biomonitoring, in conservation, biosecurity, and wildlife forensic sciences. Reptiles are high risk invasive alien species that can cause damaging environmental impacts, yet the dynamics around terrestrial reptile DNA deposition and subsequent detection are poorly understood. Concerns around the role of the pet trade in introducing key reptile pests have resulted in calls for greater biosecurity surveillance and biomonitoring tools. Emerging studies have explored the applications of trace DNA and environmental DNA (eDNA) to reptile detectability, but questions remain around DNA persistence, sample storage, and DNA degradation through time influencing biosecurity compliance uptake. Here we consider Pantherophis guttatus (American corn snake), a key vertebrate pest species in Australia, as a model organism for the study of trace DNA detection over time. Our study focussed on the application of a recently developed corn snake LAMP assay for DNA detection from biosecurity relevant samples, with a particular focus on wildlife compliance for captive reptiles and shed skin samples subject to varied storage and environmental conditions. Experiments were conducted with (i) shed skin subject to a range of storage and treatment conditions over a 10-week period, (ii) trace DNA samples deposited on newspaper, plastic, glazed terracotta, and glass for 0 to 168 h post live snake presence, and (iii) shed skin samples subject to varying environmental conditions over an 8-week period. DNA remained detectable for up to 10 weeks under different storage conditions when extracted from shed skin and for up to 168 h after live reptile contact. DNA extracted from shed skin samples subject to varied environmental conditions was detectable up to 8-weeks post deposition with increasing times to detection. Our findings strengthen the case for trace DNA detection methods being applied to monitoring of terrestrial snakes, particularly for rapid compliance, monitoring, and environmental biosecurity.

Children's exposure to brominated flame retardants in the home: The TESIE study - Kate Hoffman; Xuening Tang; Ellen M. Cooper; Stephanie C. Hammel; Andreas Sjodin; Allison L. Phillips; Thomas F. Webster; Heather M. Stapleton (Environmental Pollution, 2024)

Adapting the Marine Stewardship Council risk-based framework to estimate impacts on seabirds, marine mammals, marine turtles and sea snakes - Stephanie D. Good; Kate Dewar; Polly Burns; Keith Sainsbury; Richard A. Phillips; Bryan P. Wallace; Caterina Fortuna; Vinay Udyawer; Bruce Robson; Edward F. Melvin; Rohan J.C. Currey (Marine Policy, 2024)

Conservation prioritisation of genomic diversity to inform management of a declining mammal species - Brenton von Takach; Skye F. Cameron; Teigan Cremona; Mark D.B. Eldridge; Diana O. Fisher; Rosemary Hohnen; Chris J. Jolly; Ella Kelly; Ben L. Phillips; Ian J. Radford; Kate Rick; Peter B.S. Spencer; et al. (Biological Conservation, 2024)

Canopy hedge pruning in pecan production differentially affects groups of arthropod pests and associated natural enemies - Pedro F.S. Toledo; Kate Phillips; Jason M. Schmidt; Clive H. Bock; Colin Wong; William G. Hudson; David I. Shapiro-Ilan; Lenny Wells; Angelita L. Acebes-Doria (Crop Protection, 2024)

Characterizing azobenzene disperse dyes and related compounds in house dust and their correlations with other organic contaminant classes - Kirsten E. Overdahl; Christopher D. Kassotis; Kate Hoffman; Gordon J. Getzinger; Allison Phillips; Stephanie Hammel; Heather M. Stapleton; P. Lee Ferguson (Environmental Pollution, 2023)

Development of a qPCR detection approach for pathogenic Burkholderia cenocepacia associated with fresh vegetables - Aixin Liu; Kate Phillips; Jiayuan Jia; Peng Deng; Dunhua Zhang; Sam Chang; Shi-En Lu (Food Microbiology, 2023)

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

Sex differences in the physiological adaptations to heat acclimation: a state-of-the-art review - Kate A. Wickham; Phillip J. Wallace; Stephen S. Cheung (European Journal of Applied Physiology, 2021)

The effects of weather, group size and type of nest on the timing of egg-laying in the Southern Ground-hornbill Bucorvus leadbeateri - Kate F. Carstens; Reshma Kassanjee; Rob M. Little; Peter G. Ryan; Phillip A. R. Hockey (Journal of Ornithology, 2019)

Soil carbon cycling proxies: Understanding their critical role in predicting climate change feedbacks - Vanessa L. Bailey; Ben Bond‐Lamberty; Kristen DeAngelis; A. Stuart Grandy; Christine V. Hawkes; Kate Heckman; Kate Lajtha; Richard P. Phillips; Benjamin N. Sulman; Katherine E. O. Todd‐Brown; Matthew D. Wallenstein (Global Change Biology, 2018)
The complexity of processes and interactions that drive soil C dynamics necessitate the use of proxy variables to represent soil characteristics that cannot be directly measured (correlative proxies), or that aggregate information about multiple soil characteristics into one variable (integrative proxies). These proxies have proven useful for understanding the soil C cycle, which is highly variable in both space and time, and are now being used to make predictions of the fate and persistence of C under future climate scenarios. However, the C pools and processes that proxies represent must be thoughtfully considered in order to minimize uncertainties in empirical understanding. This is necessary to capture the full value of a proxy in model parameters and in model outcomes. Here, we provide specific examples of proxy variables that could improve decision‐making, and modeling skill, while also encouraging continued work on their mechanistic underpinnings. We explore the use of three common soil proxies used to study soil C cycling: metabolic quotient, clay content, and physical fractionation. We also consider how emerging data types, such as genome‐sequence data, can serve as proxies for microbial community activities. By examining some broad assumptions in soil C cycling with the proxies already in use, we can develop new hypotheses and specify criteria for new and needed proxies.

Telomere length measurement by qPCR in birds is affected by storage method of blood samples - Sophie Reichert; Hannah Froy; Winnie Boner; Theresa M. Burg; Francis Daunt; Robert Gillespie; Kate Griffiths; Sue Lewis; Richard A. Phillips; Dan H. Nussey; Pat Monaghan (Oecologia, 2017)

A global analysis of the determinants of alien geographical range size in birds - Ellie E. Dyer; Victoria Franks; Phillip Cassey; Ben Collen; Robert C. Cope; Kate E. Jones; Çagan H. Şekercioğlu; Tim M. Blackburn (Global Ecology and Biogeography, 2016)
Aim Determining the causes of range size variation in the distributions of alien species is important for understanding the spread of invasive species. Factors influencing alien range size have been explored for some species at a regional level, but to date there has been no global analysis of an entire class. Here, we present such an analysis for birds, testing for the effects of introduction event, location and species‐level variables on alien range sizes. Location Global. Methods We used a novel dataset on the global distributions of alien bird species to test for relationships between alien range size and colonization pressure, residence time, extent of the global climatic niche, native range size, body mass and specialization, using a statistical approach based on phylogenetic generalized least squares models. We performed this analysis globally, and for separate biogeographical realms. Results Approximately half of the variation in alien bird range size is explained by colonization pressure in univariate analysis. We identified consistent effects of higher colonization pressure at global and realm levels, as well as support for effects of native range size and residence time. We found less support for effects of body mass, specialization or extent of the global climatic niche on alien range size. Main conclusions Alien bird range sizes are generally small relative to their native range sizes, and many are continuing to expand. Nevertheless, current variation is predictable, most strongly by the event‐level factor of colonization pressure. Whether a species is widespread is a better predictor of alien range size than whether a species could be widespread (estimated by global climatic niche extent), while we also find effects of residence time on alien range size. These relationships may help to identify those alien species that are more likely to spread and hence have greater environmental and economic impacts where they have been introduced.

Developing building-damage scales for lahars: application to Merapi volcano, Indonesia - Susanna F. Jenkins; Jeremy C. Phillips; Rebecca Price; Kate Feloy; Peter J. Baxter; Danang Sri Hadmoko; Edouard de Bélizal (Bulletin of Volcanology, 2015)

Cation exchange capacity of density fractions from paired conifer/grassland soils - Sarah I. Beldin; Bruce A. Caldwell; Phillip Sollins; Elizabeth W. Sulzman; Kate Lajtha; Susan E. Crow (Biology and Fertility of Soils, 2007)

Chemistry and Dynamics of Dissolved Organic Matter in a Temperate Coniferous Forest on Andic Soils: Effects of Litter Quality - Yuriko Yano; Kate Lajtha; Phillip Sollins; Bruce A. Caldwell (Ecosystems, 2005)

Influences on the transport and establishment of exotic bird species: an analysis of the parrots (Psittaciformes) of the world - Phillip Cassey; Tim M. Blackburn; Gareth J. Russell; Kate E. Jones; Julie L. Lockwood (Global Change Biology, 2004)
Most studies of exotic species invasions only consider the factors that affect the establishment of populations following release, yet this is only one step on the invasion pathway. Different factors are likely to influence which species are transported and released. Here, we examine the influence of species traits on the successful transition of species through several stages in the introduction pathway (transport, release, and establishment), using parrots (Aves: Psittaciformes) as a model system. We use a species‐level supertree of parrots to test for phylogenetic auto‐correlation in the introduction process. Our analyses find that different sets of variables are related to the probability that a species enters each stage on the invasion pathway. The availability of individuals for transport and release seems to be most important for passage through these stages, but has no obvious effect on establishment following release. Rather, establishment success is higher for sedentary species, and species with broad diets.

The influence of spatial resolution on macroecological patterns of range size variation: a case study using parrots (Aves: Psittaciformes) of the world - Tim M. Blackburn; Kate E. Jones; Phillip Cassey; Neil Losin (Journal of Biogeography, 2004)
Aim To assess the extent to which the resolution at which geographical range sizes are measured influences macroecological patterns in this variable. Location Global. Methods Data on the geographical ranges of parrot species were digitized, and a Geographic Information System used to produce nine range size estimates for each species using different degrees of spatial resolution. The inter‐correlation of these estimates was then compared, together with their patterns of covariation with population size, body mass and migratory behaviour (across species and controlling for phylogeny), their pattern of phylogenetic correlation, and the frequency distributions of the different measures. Results Strong correlations exist among all nine range size measures across species, albeit that measures of similar spatial resolution are more strongly correlated. All measures show similar patterns of covariation with population size, body mass and migratory behaviour, and similar patterns of phylogenetic correlation. The skewness of frequency distributions increases towards zero as the resolution of the range size measure declines. Main conclusions The results of macroecological analyses are little affected by the resolution with which geographical range sizes are calculated, at least for the parrots of the world. Previously published studies based on crude measures of range size would be unlikely to have produced markedly different conclusions had they used more refined range size metrics.

Mistakes in the analysis of exotic species establishment: source pool designation and correlates of introduction success among parrots (Aves: Psittaciformes) of the world - Phillip Cassey; Tim M. Blackburn; Kate E. Jones; Julie L. Lockwood (Journal of Biogeography, 2004)
Aim To evaluate the effect of mis‐specifying the correct comparison of species pools in the study of species characteristics associated with the biological introduction of exotic species. Methods We use a high quality data set on biological introductions of parrots (Aves: Psittaciformes). These data allow us to examine relationships between life history traits and probability of successful transition through an introduction stage when the species pool is both correctly and incorrectly specified. Results For the establishment of introduced parrot species, nearly half of the predictor variables showed different patterns of significance when an incorrect pool was specified. Multivariate analysis identified entirely different sets of variables as independent predictors of establishment success, depending on the species pool used. Correct pool specification identified that introduced parrot species have been more likely to establish if they have broader diets and are more sedentary. Main conclusions Conclusions from the analysis of biological introductions are likely to depend on the specification of the species pool for such analyses. In the analysis of parrot introductions, this was particularly apparent in establishment success following release. Further studies that analyse the introduction pathway need to examine the effects of pool mis‐specification so that the generality of our results can be assessed.